Medical nutrition therapy of pediatric type 1 diabetes mellitus in India: Unique aspects and challenges. Issue 1 (10th August 2020) - Salis, Sheryl; Joseph, Mini; Agarwala, Anuja; Sharma, Rajni; Kapoor, Nitin; Irani, Aspi J.
Abstract: Medical nutrition therapy (MNT) is a vital aspect of management of type 1 diabetes mellitus (T1DM) and should be tailored to ethnic and family traditions and the socioeconomic and educational status of the patient. In this article, we discuss the unique aspects of MNT in children and adolescents with T1DM in the Indian setting, with focus on the challenges faced by patients, dieticians and physicians and how these can be overcome. The authors reviewed the available literature on MNT in T1DM from India and prepared the document based on their vast collective clinical experience in treating patients with T1DM from different regions in India. Indian diets are predominantly carbohydrate‐based with high glycemic index (GI) and low protein content. Various methods are available to increase the protein and fiber content and reduce the GI of food in order to limit glycemic excursions. Insulin regimens need to be tailored to the child's school timings, meal schedule, and the availability of a responsible adult to supervise/administer insulin. All patients, irrespective of economic and education background, should be taught the broad principles of healthy eating, balanced diet and carbohydrate counting. There are various barriers to dietary compliance, including joint family system, changing lifestyles, and other factors which need to be addressed. There is a need to customize dietary management according to patient characteristics and needs and develop standardized patient educational material on principles of healthy eating in various regional languages.